Temperature Variation and Host Immunity Regulate Viral Persistence in a Salmonid Host - David J. Páez; Rachel L. Powers; Peng Jia; Natalia Ballesteros; Gael Kurath; Kerry A. Naish; Maureen K. Purcell (Pathogens, 2021)
Environmental variation has important effects on host–pathogen interactions, affecting large-scale ecological processes such as the severity and frequency of epidemics. However, less is known about how the environment interacts with host immunity to modulate virus fitness within hosts. Here, we studied the interaction between host immune responses and water temperature on the long-term persistence of a model vertebrate virus, infectious hematopoietic necrosis virus (IHNV) in steelhead trout (Oncorhynchus mykiss). We first used cell culture methods to factor out strong host immune responses, allowing us to test the effect of temperature on viral replication. We found that 15 <semantics>∘</semantics>C water temperature accelerated IHNV replication compared to the colder 10 and 8 <semantics>∘</semantics>C temperatures. We then conducted in vivo experiments to quantify the effect of 6, 10, and 15 <semantics>∘</semantics>C water temperatures on IHNV persistence over 8 months. Fish held at 15 and 10 <semantics>∘</semantics>C were found to have higher prevalence of neutralizing antibodies compared to fish held at 6 <semantics>∘</semantics>C. We found that IHNV persisted for a shorter time at warmer temperatures and resulted in an overall lower fish mortality compared to colder temperatures. These results support the hypothesis that temperature and host immune responses interact to modulate virus persistence within hosts. When immune responses were minimized (i.e., in vitro) virus replication was higher at warmer temperatures. However, with a full potential for host immune responses (i.e., in vivo experiments) longer virus persistence and higher long-term virulence was favored in colder temperatures. We also found that the viral RNA that persisted at later time points (179 and 270 days post-exposure) was mostly localized in the kidney and spleen tissues. These tissues are composed of hematopoietic cells that are favored targets of the virus. By partitioning the effect of temperature on host and pathogen responses, our results help to better understand environmental drivers of host–pathogen interactions within hosts, providing insights into potential host–pathogen responses to climate change.